2005
DOI: 10.1097/00001756-200512190-00009
|View full text |Cite
|
Sign up to set email alerts
|

Extracting rules: early and late mismatch negativity to tone patterns

Abstract: The auditory processing of physical stimulus features can be measured by the mismatch negativity. Past studies have shown that higher-order stimulus features also elicit a mismatch negativity. In some studies, a second component, termed late mismatch negativity, has been observed; yet the functional significance of this component remains unclear. We tested two-tone-pattern stimuli following an abstract rule in healthy adults. As expected, the tone pattern elicited a significant mismatch negativity peaking at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 22 publications
10
55
0
Order By: Relevance
“…It has been suggested that the LDN response reflects processes of letter-speech sound integration, attention, long-term memory transfer, or further cognitive processing of the sound change (Ceponiene et al, 2004;Cheour et al, 2001;Froyen et al, 2009;Shestakova et al, 2003;Zachau et al, 2005). In the present study, no letter-speech sound integration was possible in the experimental paradigm, and the sine-wave tones would be unlikely to activate long-term memory representations or to require the storage of complex rules.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It has been suggested that the LDN response reflects processes of letter-speech sound integration, attention, long-term memory transfer, or further cognitive processing of the sound change (Ceponiene et al, 2004;Cheour et al, 2001;Froyen et al, 2009;Shestakova et al, 2003;Zachau et al, 2005). In the present study, no letter-speech sound integration was possible in the experimental paradigm, and the sine-wave tones would be unlikely to activate long-term memory representations or to require the storage of complex rules.…”
Section: Discussionmentioning
confidence: 52%
“…However, its function is still unknown, with suggestions of involvement in further cognitive processing of the sound change, long-term memory storage, or activation of attention mechanisms (Ceponiene et al, 2004;Cheour et al, 2001;Shestakova et al, 2003;Zachau et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies (e.g. Zachau et al, 2005) have associated the late negativity with neural processes of auditory rule extraction. Under this interpretation of the late negativity component, the larger late negativity in the perception-plusproduction group may indicate that to some extent the perception-plus-production group is better at tone extraction at the unintentional level compared with the perception-only BRES : 44353 1030 1031 1032 1033 1034 1035 1036 1037 1038 1039 1040 1041 1042 1043 1044 1045 1046 1047 1048 1049 1050 1051 1052 1053 1054 1055 1056 1057 1058 1059 1060 1061 1062 1063 1064 1065 1066 1067 1068 1069 1070 1071 1072 1073 1074 1075 1076 1077 1078 1079 1080 1081 1082 1083 1084 1085 1086 1087 1088 1089 1090 1091 1092 1093 1094 1095 1096 1097 1098 1099 1100 1101 1102 1103 1104 1105 1106 1107 1108 1109 1110 1111 1112 1113 1114 111...…”
Section: Perception-only Training Vs Perception-plusproduction Trainingmentioning
confidence: 97%
“…The generator of this component has been measured over right central-parietal areas (Hommet et al 2009). The functional significance of the late MMN has been less intensively investigated in comparison to the classical MMN component, however its significance is believed to be related to attention related processes (Shestakova et al 2003), to long term memory (Zachau et al 2005) and to letter-speech sound integration (Froyen et al 2009). In dyslexia reduced amplitude of the MMN and the late MMN component to speech stimuli in children (Schulte-Körne et al 1998a;Lachmann et al 2005) and adults (Schulte-Körne et al 2001b) as well as a longer MMN latency in response to speech stimuli (Corbera et al 2006;Alonso-Bua et al 2006) were repeatedly found and interpreted as a neurophysiologic correlate of impaired discrimination of speech sounds.…”
Section: Speech Perception In Dyslexiamentioning
confidence: 99%